Pengembangan Novel Grafik Elektronik pada Materi Reaksi Radikal Bebas sebagai Media Suplemen Pembelajaran - Sabianto, Fransiskus; Melati, Husna Amalya; Muharini, Rini (Universitas Negeri Semarang, 2022)
This research was aimed to produce a valid electronic graphic novel on free radical reaction subject and to find out the student’s response to the developed product. This research employed Research Development (RD) method by using Thiagarajan’s 4D model with modification, in which applied only three of four steps in 4D model. The developed product was validated by experts. The responses toward developed product were collected from the students of Chemistry Education FKIP Untan who have taken organic chemistry course. Data collection tools used were validation sheets and student’s response questionnaires on the developed product. The validation’s result from the experts showed that the developed product was very proper in terms of content, presentation, linguistic, and graphic aspects with consecutive total scores of 94.0%, 95.0%, 89.0%, and 100,00% respectively. The results of the student’s responses in small group trials and in large group trials were of 82.5% with high category and of 83.2% with very high category, respectively. Thus, this electronic graphic novel on radical reaction has very good potential as a learning media to attract students to learn free radical reaction and its application in daily life.